Obstacles of enterprises moving towards the next generation internet. (4th August 2005) - Shiau, Wen-Lung; Chao, Han-Chieh; Hsu, Ping-Yu
The next generation internet (NGI) has already been deployed, but few enterprises actually migrate to it. What is wrong with the NGI? In this paper, we build an NGI testing bed. In our tests, we set up a current network environment and an NGI environment to simulate a real enterprise using the internet. The results show that the overall environment of NGI has not yet caught up with the functionality of the current network. The best way to remove these obstacles faced by enterprises moving towards next generation internet is to continuously improve the supporting infrastructure of the NGI such as internet service provider (ISP) supports, development tools, and enterprise applications.